A study on perceptions about the roles portrayed by women in magazine advertisements - Kıvanç, Yeşim. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
In this thesis, the roles portrayed by women in magazine advertisements and the perception of the male and female magazine readers about this subject will be studied. The roles portrayed by women in magazine advertisements are examined by looking at the content of the ads, and also the opinions of magazine readers are asked about thiu topic. Three types of advertisements are shown to subjects. The first one portrays the woman as working, the second one shows the woman as a housewife, whereas the third one illustrates her as an alluring model. Perceptions about these advertisements are taken from both male and female subjects and differences among their ideas are evaluated. Also the relationship among variables, which are used in the study, and demographics are analysed. As a result, it is seen that, males and females do not share the same ideas about role portrayals of women in magazine advertisements. While females criticize exaggerated roles of women in magazine advertisements / males accept that they are attracted by beautiful women. It is understood that, the appropriate match between the model and the gender image of product, the setting of the portrayal and the portrayal's realism are very important for both sex. The study includes the literature review and the field study which is conducted through a questionnaire. In order to learn their ideas about role portrayals of women, equal number of men and women are given questionnaires. The interpretation of these data is done through computer and implications for marketers and academicians are presented.
Keywords: Women in advertising.; Advertising -- Social aspects.